The application of nitrogen oxides in industrial preparations of nitro compounds. (5th July 2018) - Gao, Xi; Peng, Xinhua; Chen, Kaihao
Abstract: Nitrogen oxides of atomic economy are promising nitrating agents instead of common nitric and sulphuric acids in the industrial preparations of nitro compounds. This review provides recent developments of nitration using nitrogen oxides found in applied research. Novel nitration involving three classes of nitrogen oxides is described for the synthesis of organic intermediates, medicinally relevant compounds, natural products, high energy density materials, and some catalytic materials.